DESAIN MODEL ASESMEN PEMBELAJARAN UNTUK MAHASISWA CALON GURU BIOLOGI FKIP UNIVERSITAS RIAU - Febryani, Shelvi Febryani; ', Firdaus LN; ', Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research is to design green pedagogy Assessment Model Green for student teachers FKIP Biology, University of Riau (UR). Assessment models used are authentic assessment and reflective assessment. The authentic assessmet consist of seven techniques, there are: paper and pencil test, attitude, performance, product, project, self-assessment and portofolio. The research was conducted at Biology Education University of Riau and the limiting test with twenty student on January until June 2015. The kind of this research is research and Development (R & D) design with ADDIE (analyze, desaign, develop, implement and evaluate) model. This research just up develop stage. Data collection instruments used were validation sheet, observation sheet, interview sheet and questionnaire. Validation sheet is value by 3 external validator. Observation sheet used to observe environment of UR. Interview was conducted directly with a field manager ESU UR. The questionnaire used to determine the feasibility and used of products have been developed. Data collected were statistically analyzed descriptively. Results of the validation on KD 1.1 is 3.25 with a valid category. Results of the validation on KD 1.2 is 3.26 with a valid category. Results of the validation on KD 1.3 is 3.24 with a valid category. Results of the validation on KD 1.4 is 3.27 with a valid category. To determine used product, then do limited testing. From result of research that has been done can be seen that the design of the green pedagogy assessment model was conducted by used ADDIE model of which is through the stage of Analyze, Design, Develop is valid and can be implemented through testing with a larger scale. Key words: biology students, green pedagogy, assessment model